Factors associated with pacifier use among children of working women with childcare in the workplace - Santos, Thais Rosa Dos; Buccini, Gabriela Dos Santos; Sebastião, Luciana Tavares (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACTPurpose: to identify the prevalence of pacifier use as well as the reasons for introducing a pacifier and to analyze factors associated with this practice among children of working women with childcare in the workplace.Methods: a cross-sectional study was conducted with 46 women working at a higher education institution that offered childcare in the workplace; the children were in the age range 2.6 years. Data collection was carried out using a self-report questionnaire filled at home. Reasons for introducing a pacifier were analyzed descriptively; Poisson regression was used in the multiple analysis.Results: the prevalence of pacifier use was 63%. Most women offered the pacifier after the infant's 16th day of life, in order to calm the baby. In the multiple analysis, higher maternal education was associated with pacifier use.Conclusion: a high prevalence of pacifier use was observed, as well as early pacifier introduction, among children of working women with childcare in the workplace. With regard to the factors associated with pacifier use in this population, lower maternal education acted as a protective factor against pacifier use.

RESUMOObjetivo: identificar a prevalência de uso da chupeta e os motivos para sua introdução além de analisar os fatores associados a essa prática entre filhos de mulheres com creche no local de trabalho.Métodos: estudo transversal realizado com 46 mulheres trabalhadoras de uma Instituição de Ensino Superior com creche no local de trabalho, mães de crianças com idade média de 2,6 anos. Para coleta de dados, utilizou-se questionário enviado para casa. Procedeu-se análise descritiva dos motivos da introdução da chupeta e para a análise múltipla utilizou-se regressão de Poisson.Resultados: a prevalência do uso de chupeta foi de 63%. A maioria ofereceu a chupeta após o 16º dia, com o intuito de acalmá-la. Na análise múltipla, a maior escolaridade materna associou-se ao uso de chupeta.Conclusão: constatou-se a alta prevalência de uso e introdução precoce de chupeta entre filhos de mulheres trabalhadoras com creche no local de trabalho. Com relação aos fatores associados ao uso de chupeta nesta população verificou-se a menor escolaridade das mães como fator de proteção ao uso de chupeta.
Fatores associados ao uso de chupeta entre filhos de mulheres trabalhadoras com creche no local de trabalho
Keywords: Working Women; Child Health; Pacifier; Speech, Language and Hearing Sciences; Trabalho Feminino; Saúde da Criança; Chupeta; Fonoaudiologia